Pemanfaatan Tumbuhan Diwoka (Piper Macropiper Pennant) oleh Suku Dani, Wamena - KONSTANTINA M. B KAMEUBUN; ROSANIA REHIARA; FRANS DEMINGGUS (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2020)
Ethnobotanical and taxonomical studies are conducted to uncover the scientific name, uses as well as utilization of Diwoka (local name) popular to the Dani people in Wamena. The local name, Diwoka, is determined by its scientific name Piper macropiper Pennant. Piper macropiper has been used by the Dani people to serve as spices when foods are cooked traditionally by stone-fired earth oven (bakarbatu) or prepared in other ways such as stir-frying vegetables, fish, and meat. The leaves can be consumed uncooked the way salad is consumed beside it is functioned as medicine as well. The distribution of this type of plant is found in Indonesia, Papua New Guinea, Solomon Islands, Australia (Northern territory), Brunei, and Sri Lanka